Efficacy of Common Spices on Improving Serum Lipids in Individuals with Type 2 Diabetes: Systematic Review and Meta-Analysis of Clinical Trials. (29th May 2020) - Alasvand, Sepideh; Bridges, William; Haley-Zitlin, Vivian
Abstract: Objectives: This systematic review and meta-analysis explored efficacy of common spices cardamom, ginger, cumin, curcuminoids and cinnamon on improving serum lipid levels in people with type 2 diabetes. Methods: Databases PubMed, FSTA, Web of Science, CINAHEL, MEDLINE and Cochrane Library database of systematic review were searched using keywords ("Serum lipids" OR triglyceride* OR cholesterol* OR "LDL" OR "HDL" OR dyslipidemia) AND (Ginger or zingiber or "zingiber officinale" or "cinnamomum zeylanicum" or "cinnamomum aromaticum" or "cinnamomum cassia" or "cinnamomum verum" or curcumin or turmeric or curcuminoids or "curcuma longa" or langas or "curcuma zedoarias" or turmeric) AND (diabetes* OR "diabetes mellitus" OR "type 2" OR "blood glucose" OR insulin* OR antidiabet* OR "glucose level") up to January 2020. Statistical calculations used SAS software version 9.2 (SAS, Cary NC, USA). Results: Of 636 studies, 27 met the meta-analysis selection criteria, with 5698 trial participants total. The spices significantly improved TC, TG, and LDL-C, with no significant effect on HDL-C. The reduction in intervention vs. control was: TC, −5.0912 mg/dl, 95% CI (−18.7167, −0.7804), P value 0.038; TG, −9.7486 mg/dl, 95% CI (−33.9445, −5.8260), P value 0.33; LDL-C, −4.653 mg/dl, 95% CI (−8.686, −0.6212), P value 0.02. No significant effect on HDL-C was seen (−0.019 mg/dl, 95% CI (−0.72, 0.68), P = 0.95. Heterogeneity was observed across all 27 studies. Conclusions: Spices examined exhibited a significant reduction in TG, TC and LDL-C levels among patients with type 2 diabetes with no effect on HDL-C levels suggesting a role for spices as a dyslipidemic agent. Funding Sources: Clemson University.